PENERAPAN PROSES PEMBELAJARAN KREATIF DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Dinda Prilliani; Debora Ginting (Universitas Negeri Medan, 2023)
The purpose of this research is to study the application of creative learning and the role of the teacher so that students' motivation in class 1-A at SD Negeri 085115 Sibolga can increase. This research was conducted because there was a problem of low student motivation in learning. This study used qualitative research methods. Data analysis was carried out by going through the data reduction stage, and then the data obtained was presented in the form of a qualitative description. Data was collected through observation, interviews, field notes and documentation. The research results show that learning in class 1-A SDN 085115 Sibolga is focused on students with the aim of creating a comfortable, safe and enjoyable learning atmosphere. Teachers play an important role in designing innovative and interesting learning methods to increase student motivation. The use of IT-based media and collaboration models and games are also used to stimulate students' thinking and thinking. Various teaching models are used to increase student motivation and teachers encourage critical thinking through challenging questions, exploring ideas, and understanding topics. In addition, the teacher also gives praise and appreciation as an effective way to acknowledge students' efforts in learning.